Efficiency of modern preparations at spontaneous oesophagostomosis of pigs - Манойло, Ю. Б. (Scientific Progress & Innovations, 2016)
In the article we presented the results of scientific researches on studying efficiency of modern preparations on the spontaneous oesophagostomosis of pigs that can improve extensefficiency and intensefficiency of anthelmintics using probiotics and prebiotics. It is established that the use of feed additives in combination with anti-parasitic preparations improves therapeutic efficiency of «Brovermectin» 2 % water-soluble at oesophagostomosic invasion of pigs. We proved that the enzyme-probiotic preparations contribute to the increase average of daily weight gain and increases affect of the preservation of piglets.